REAKTUALISASI PEMAHAMAN HAKIKAT DAN TUJUAN PERKAWINAN MENUJU KELUARGA SAKINAH - Lisnawati Lisnawati (Institut Agama Islam Negeri Batusangkar, 2022)
This type of research is normative legal research using an Islamic law approach. The results of this study indicate that the reactualization of understanding the truth and purpose of marriage is one of the efforts that can be done to prevent the occurrence of various household problems, especially divorce, namely by understanding the great values and realizing that marriage does not only have horizontal dimensions but also vertical dimensions as worship to Allah swt. The sakinah family has a condition that is decorated with mawaddah and raḥmah. The indicator of a sakinah family is the functioning of the family. commitment is needed to keep the family function running well, which in the end will create a sakinah family.